Design, construction and results of a test system of real electrical machines to be used in wave energy (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In the wave energy converters (WEC), the transformation of mechanical energy through electrical machines is key, as well as their effect on the dynamics of the whole system. This work presents the design, construction and results of a hardware device to test different real rotating electrical machines and their associated power electronics, interacting with the mathematical model of a WEC. A floating device anchored to the seabed was considered. Wave action heels the device, which moves a mass inside. The linear motion of the mass is transformed into a rotary motion to drive an electric machine, which transforms mechanical energy into electrical energy. Power generation results and the best control strategy are presented for wave heights of 1, 2, and 4 m, with periods of 6, 9, and 12 s. For small and medium wave heights, the constant torque and constant power control strategies were the best. For waves of 4 m and 9 s, the quadratic torque strategy showed the best energy results. The presented device, allows the evaluation of different electrical machines and their control strategies on a real laboratory scale, as well as their influence on the dynamics of the WEC.